Ժողովրդական մանրապատում ստեղծագործությունները Լ. Հարությունյանի «Նշխարներ Արցախի բանահյուսության» ժողովածուներում - Աթայան, Անահիտ (ԱրՊՀ հրատ․)
В статье “Народные эскизы в сборниках Левона Арутюняна “Реликвии фольклора Арцаха” обсуждаются материалы пяти сборников, комментируя примеры эскизов, касающихся жизни, истории, быта, традиций арцахца. Деятельность Л.Арутюняна носит целенаправленный характер, научно обусловлен, связан с культурой народа Арцаха, зарождением, развитием его устного творчества, несущем изменения в различные исторические периоды. Эскизы в пяти сборниках Левона Арутюняна свидетельствуют о высокой морали, гордом быте, природном даре, умственном восприятии народа. In the articles ''Folk sketches in the collections of Levon Hayrapetyan'', ''Relics of Artsakh folklore'' the materials of 5 collections of the authorare discussed, interpreting samples of sketches related to life, history, mode of life, Artsakh traditions. The activity of LevonHayrapetian has a purposeful character, scientifically proved, connected with the culture of Artsakh people, generation, with the development of the spoken creativity that brings changes todifferent historical periods. Sketches in the 5 collections of LevonHayrapetian witness about the high moral, proud mode of life, natural gift and mental perception of the people.
Keywords: Բանահյուսություն; Արցախ